2019
DOI: 10.1002/lio2.233
|View full text |Cite
|
Sign up to set email alerts
|

Calcium electroporation for recurrent head and neck cancer: A clinical phase I study

Abstract: Background Calcium electroporation is a novel cancer treatment, which combines temporary cell permeability from electroporation with a high influx of calcium intracellularly resulting in cancer cell necrosis. Methods A phase I trial performing calcium electroporation on 6 patients suffering from recurrent head and neck cancer. In general anesthesia, intratumoral calcium injections were followed by electroporation. Safety was monitored by adverse events registration, ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 36 publications
(83 reference statements)
0
41
1
2
Order By: Relevance
“…Preclinical studies provided the first support for the efficacy across cancer histologies, as well as an explanation of the mechanisms of action [11,13,14,[20][21][22][23][24][25][26][27]. The results of the first clinical trials suggested that Ca-EP is safe and efficient at the local level for tumours of different types, including cutaneous metastases from breast cancer and malignant melanoma and recurrent head and neck cancer [11,20]. Moreover, a case report showed that Ca-EP is able to initiate a systemic immune response and target untreated metastases in a patient suffering from malignant melanoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…Preclinical studies provided the first support for the efficacy across cancer histologies, as well as an explanation of the mechanisms of action [11,13,14,[20][21][22][23][24][25][26][27]. The results of the first clinical trials suggested that Ca-EP is safe and efficient at the local level for tumours of different types, including cutaneous metastases from breast cancer and malignant melanoma and recurrent head and neck cancer [11,20]. Moreover, a case report showed that Ca-EP is able to initiate a systemic immune response and target untreated metastases in a patient suffering from malignant melanoma [28].…”
Section: Discussionmentioning
confidence: 99%
“…After the first clinical trial using calcium electroporation, several studies commenced ( Table 2). A phase I study treating recurrent mucosal head and neck cancer patients with calcium electroporation has recently been published [120]. Six patients that were previously irradiated, deemed inoperable, and without further treatment options, were included in the trial testing safety of the treatment on larger mucosal head and neck cancers.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…Initial clinical studies have used a high dose of calcium (220-225 mM in a volume equivalent to 50% of the tumor volume) but data also points to lower doses of calcium being effective [61,116]. This needs to be further investigated; nonetheless, for a safety point of view high doses of calcium were well tolerated [19,120].…”
Section: Perspectivesmentioning
confidence: 99%
“…Calcium electroporation is a prospective novel anticancer treatment, showing promising response rates in preclinical and clinical trials [3][4][5][6][7]. High calcium concentrations are introduced to the cell cytosol by electroporation, a method where short, high-voltage pulses permeabilize the cell membrane, allowing for passage of non-permeant ions and molecules, e.g., calcium [4,7].…”
Section: Of 12mentioning
confidence: 99%